Performance of SRI rice-mustard cropping system under system based integrated nutrient management practices - Nayak, Anshuman; Maity, S K; Roul, P K; Khanda, C M; Mohanty, T R (ORYZA-An International Journal of Rice, 2018)
System based integrated nutrient management practices for SRI rice-mustard cropping system was studied in a field experiment during 2013-14 and 2014-15 at RRTTS, Bhawanipatna, Kalahandi, Odisha. Application of 100% recommended dose of fertilizer (RDF-120:60:60 kg N:P2O5: K2O ha-1) + 5t FYM ha-1 with split application of nitrogen as ¼ at transplanting(TP) ½ at active tillering (AT) and ¼ at panicle initiation (PI) recorded maximum effective tillers m-2 (183), filled grains panicle-1 (213), test weight ( 26.4 g) and grain yield (7.54 t ha- 1) of rice under SRI. The increase in yield in this best INM treatment was 59.07% higher over existing practice of application of 100% RDF with split application of nitrogen as 1 3 at TP, 1 3 at AT and 1 3 at PI. The highest residual effect on mustard seed yield (0.81 t ha-1), system productivity (9.63 t ha-1), net return (Rs. 82,488/- ha- 1) and return rupee-1 invested (2.55) was noticed with this treatment. As regards to the nutrient management in mustard, higher seed yield of mustard (0.80 t ha-1), system productivity ( 7.98 t ha-1), net return (Rs 59,163/- ha- 1) and return rupee-1 invested (2.11) was recorded with application of 50% RDF (RDF-40:20:20 kg N:P2O5: K2O ha-1) + bio-fertilizer to mustard which was at par with 100%RDF treatment. The yield of mustard in this best treatment was 90.47% higher over control.